2018
DOI: 10.5194/acp-18-1729-2018
|View full text |Cite
|
Sign up to set email alerts
|

Volatility measurement of atmospheric submicron aerosols in an urban atmosphere in southern China

Abstract: Abstract. Aerosol pollution has been a very serious environmental problem in China for many years. The volatility of aerosols can affect the distribution of compounds in the gas and aerosol phases, the atmospheric fates of the corresponding components, and the measurement of the concentration of aerosols. Compared to the characterization of chemical composition, few studies have focused on the volatility of aerosols in China. In this study, a thermodenuder aerosol mass spectrometer (TD-AMS) system was deployed… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

16
39
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(56 citation statements)
references
References 69 publications
(90 reference statements)
16
39
1
Order By: Relevance
“…In addition, OA consisted of ∼ 13 % extremely lowvolatility compounds (ELVOCs with C * ≤ 10 −4 µg m −3 ), consistent with the remaining organic mass fraction at 226 • C (9 %). The SVOC fraction in Beijing in summer 2018 was overall larger than those reported in Finokalia (30 %-60 %) (Lee et al, 2010), Athens (38 %) (Louvaris et al, 2017), Centreville and Raleigh (60 %) (Saha et al, 2017), and Mexico City (39 %-73 %; Cappa and Jimenez, 2010). Such results might suggest relatively higher volatility of OA in summer in Beijing than at other sites, consistent with the fact that the fraction of evaporated particulate organics (28 %) at 50 • C was larger than that observed in Shenzhen (∼ 10 %) , Centreville and Raleigh (Kostenidou et al, 2018;Saha et al, 2017), and Athens (Louvaris et al, 2017).…”
Section: Estimation Of Oa Volatility Distributionmentioning
confidence: 69%
See 1 more Smart Citation
“…In addition, OA consisted of ∼ 13 % extremely lowvolatility compounds (ELVOCs with C * ≤ 10 −4 µg m −3 ), consistent with the remaining organic mass fraction at 226 • C (9 %). The SVOC fraction in Beijing in summer 2018 was overall larger than those reported in Finokalia (30 %-60 %) (Lee et al, 2010), Athens (38 %) (Louvaris et al, 2017), Centreville and Raleigh (60 %) (Saha et al, 2017), and Mexico City (39 %-73 %; Cappa and Jimenez, 2010). Such results might suggest relatively higher volatility of OA in summer in Beijing than at other sites, consistent with the fact that the fraction of evaporated particulate organics (28 %) at 50 • C was larger than that observed in Shenzhen (∼ 10 %) , Centreville and Raleigh (Kostenidou et al, 2018;Saha et al, 2017), and Athens (Louvaris et al, 2017).…”
Section: Estimation Of Oa Volatility Distributionmentioning
confidence: 69%
“…A number of studies have been conducted to investigate the OA volatility using thermogram models assuming fixed effective vaporization enthalpy and mass accommodation coefficient (Cappa and Jimenez, 2010;Lee et al, 2010;Paciga et al, 2016;Louvaris et al, 2017;Kostenidou et al, 2018). The results showed that OA volatility distributions may vary from place to place, and the estimated OA volatility was sensitive to the assumed values of the effective vaporization enthalpy and the mass accommodation coefficient (Riipinen et al, 2010).…”
mentioning
confidence: 99%
“…For the PM 2.5 samples collected in Xi'an, filter pieces of 1.5 cm 2 were taken for OC and EC analysis using a carbon analyzer (Model 5L, Sunset Laboratory, Inc., Portland, OR, USA) following the thermal-optical transmittance protocol EUSAAR_2 (European Supersites for Atmospheric Aerosol Research; Cavalli et al, 2010). The EUSAAR_2 protocol de-fines OC1 as the carbon fraction that desorbs in helium (He) at 200 • C for 2 min.…”
Section: Determination Of Carbon Fractions By Thermal-optical Analysismentioning
confidence: 99%
“…Figure 2b shows the relative contributions of the main organic sources. The terms of low-volatility OOA (LV-OOA) and semi-volatile OOA (SV-OOA) were originally used, whilst newer studies referred to more oxidized OOA (MO-OOA) and less-oxidized OOA (LO-OOA) [22,31,35,[43][44][45]. The OOAs at different aging levels are formed through different atmospheric processes (e.g., aqueous phase reactions and photochemical reactions).…”
Section: Sources Of Particulate Mattermentioning
confidence: 99%